Clinical implications of nonsarcomeric gene polymorphisms in hypertrophic cardiomyopathy. (23rd December 2015) - García‐Honrubia, Antonio; Hernández‐Romero, Diana; Orenes‐Piñero, Esteban; Romero‐Aniorte, Ana Isabel; Climent, Vicente; García, Miriam; Garrigos‐Gómez, Noemí; Moro, Concepción; Valdés, Mariano; Marín, Francisco
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is characterized by cardiomyocyte hypertrophy and fibrosis. Although is an autosomal dominant trait, a group of nonsarcomeric genes have been postulated as modifiers of the phenotypic heterogeneity. Material and methods: We prospectively recruited 168 HCM patients and 136 healthy controls from three referral centres. Patients and controls were clinically stable at entry in the study. Nine polymorphisms previously associated with ventricular remodelling were determined: I/D ACE, AGTR1(A1666C), CYP11B2(C344T), PGC1‐α(G482S), COLIA1(G2046T), ADRB1(R389G), NOS3(G894T), RETN(‐420C>G) and CALM3(‐34T>A). Their potential influence on prognosis, assessed by hospital admissions, and their cause were recorded. Results: The median follow‐up time was 49·5 months. Allele and genotype frequencies did not differ between patients and controls. Thirty‐six patients (21·5%) required urgent hospitalization (18·5% for heart failure, 22·2% for atrial arrhythmias, 11·1% for ventricular arrhythmias, 29·6% for ischaemic heart disease, 14·8% for stroke and 3·7% for other reasons) with a hospitalization rate of 8·75% per year. Multivariate analysis showed an independent predictive value for noncarriers of polymorphic COL1A1 allele [HR: 2·76(1·26–6·05), P = 0·011] and a trend in homozygous carriers of ADRB1 Arg389 variant [HR: 1·98(0·99–4·02); P = 0·057]. Conclusion: Our study suggests that COL1A1 polymorphism (2046G>T) is an independent predictor of prognosis in HCM patients supporting the importance of nonsarcomeric genes on clinical prognosis in HCM.